Modulation of Interfacial Hydration by Carbonyl Groups in Lipid Membranes - Pérez, Hugo Alejandro (2020)
The lack of carbonyl groups and the presence of ether bonds give the lipid interphase a different water organization around the phosphate groups that affects the compressibility and electrical properties of lipid membranes. Generalized polarization of 1,2-di-O-tetradecyl-sn-glycero-3-phosphocholine (14:0 diether PC) in correlation with Fourier transform infrared (FTIR) analysis indicates a higher level of polarizability of water molecules in the membrane phase around the phosphate groups both below and above Tm. This reorganization of water promotes a different response in compressibility and dipole moment of the interphase, which is related to different H bonding of water molecules with phosphates (PO) and carbonyl (CO) groups.